Capital Structure's Role in Shaping Stock Return Dynamics: Peran Struktur Modal dalam Membentuk Dinamika Return Saham - Budi Satoto, Eko (JBMP (Jurnal Bisnis, Manajemen dan Perbankan), 2024)
This study examines the intricate relationships among capital structure, current ratio, return on assets (ROA), long-term debt-to-equity ratio, and stock returns within the property and real estate sector, utilizing a sample of 16 companies. Employing Structural Equation Modeling (SEM), capital structure is introduced as a mediating variable to elucidate its role in the association between the investigated financial metrics and stock returns. Results indicate that neither the current ratio nor ROA significantly influences stock returns, while the long-term debt-to-equity ratio negatively impacts capital structure. Surprisingly, the current ratio exhibits a positive effect on stock returns, while the long-term debt-to-equity ratio shows no significant impact. Notably, capital structure emerges as a positive determinant of stock returns. This study provides a novel perspective by introducing capital structure as a mediator, contributing to the existing body of knowledge. Practical implications suggest that property and real estate investors should consider financial ratios alongside external factors like exchange rates and economic conditions when making investment decisions. However, limitations associated with the study's focus on IDX-listed companies in this sector are acknowledged, necessitating careful interpretation of the findings.